IL-10 Induction from Implants Delivering Pancreatic Islets and Hyaluronan. (22nd July 2013) - Bollyky, Paul L.; Vernon, Robert B.; Falk, Ben A.; Preisinger, Anton; Gooden, Michel D.; Nepom, Gerald T.; Gebe, John A.
Abstract : Local induction of pro-tolerogenic cytokines, such as IL-10, is an appealing strategy to help facilitate transplantation of islets and other tissues. Here, we describe a pair of implantable devices that capitalize on our recent finding that hyaluronan (HA) promotes IL-10 production by activated T cells. The first device is an injectable hydrogel made of crosslinked HA and heparan sulfate loaded with anti-CD3/anti-CD28 antibodies and IL-2. T cells embedded within this hydrogel prior to polymerization go on to produce IL-10 in vivo . The second device is a bioengineered implant consisting of a polyvinyl alcohol sponge scaffold, supportive collagen hydrogel, and alginate spheres mediating sustained release of HA in fluid form. Pancreatic islets that expressed ovalbumin (OVA) antigen were implanted within this device for 14 days into immunodeficient mice that received OVA-specific DO.11.10 T cells and a subsequent immunization with OVA peptide. Splenocytes harvested from these mice produced IL-10 upon re-challenge with OVA or anti-CD3 antibodies. Both of these devices represent model systems that will be used, in future studies, to further evaluate IL-10 induction by HA, with the objective of improving the survival and function of transplanted islets in the setting of autoimmune (type 1) diabetes.